Development of OFDM in WDM- Radio over fiber access network - Wong, Sie Woo (2012)
Radio over Fiber (RoF) is one of the latest technologies in optical communication systems that provide effective convergence of optical and wireless access network system. RoF is a technology whereby light is modulated by a radio signal and transmitted over an optical fiber link to facilities wireless access. WavelengthDivision Multiplexing (WDM) is a multiplexing technique for fiber optic system to multiplex a number of optical carrier signals onto a single-mode fiber optic (SMF) by using difference wavelengths of laser light to carrier different signals which promising solutions to the ever increasing demand for bandwidth. Orthogonal Frequency Division Multiplexing (OFDM) technique distributes the data over a large number of carriers that are spaced apart at precise frequencies with overlapping bands. The use of FFT for modulation provides orthogonality to the sub- carriers, which prevents the demodulators from seeing frequencies other than their own. Hence by incorporating OFDM along with the optical fiber, the RoF system with WDM can be used for both short distance as well as long-haul transmission at very high data rate. This improves the system flexibility and provides a very large coverage area without increasing the cost and complexity of the system very much. This project investigates the feasibility of OFDM as a modulation technique to transmit the basebands signal over SMF. RF-to-optical up-conversion and optical-toRF down-conversion have been modeled and used as optical modulator and optical demodulator respectively. Result from Optisystem model shows the performance of OFDM signal through the WDM RoF access network. The system was utilized to carry data rates 10Gbps, the modulation type for OFDM is 4 QAM 2 bit per symbol for each channel and OFDM demodulator are employed together with coherent detection at receiver part to receive the OFDM signals over a SMF network transmission. The signal power is decreasing while the length of optical fiber was increasing for channel 1 does not apply to other channels.